Relationship between white matter lesions and regional cerebral blood flow changes during longitudinal follow up in Alzheimer's disease. Issue 7 (5th August 2015) - Hanaoka, Takuya; Kimura, Noriyuki; Aso, Yasuhiro; Takemaru, Makoto; Kimura, Yuki; Ishibashi, Masato; Matsubara, Etsuro
Abstract : Aim: The aim of the present study was to evaluate the relationship between baseline white matter lesions (WML) and changes in regional cerebral blood flow during longitudinal follow up of patients with Alzheimer's disease (AD). Methods: A total of 38 patients with AD were included in the study (16 men, 22 women; mean age 77.8 years). All patients were evaluated using the Mini‐Mental State Examination and brain perfusion single‐photon emission computed tomography at baseline with an approximately 2‐year follow up. The patients were divided into two subgroups according to the presence of WML on magnetic resonance imaging. Single‐photon emission computed tomography data were analyzed using a voxel‐by‐voxel group analysis with Statistical Parametric Mapping 8 and region of interest analysis using FineSRT. Changes in Mini‐Mental State Examination scores and regional cerebral blood flow were analyzed using the Wilcoxon signed‐rank test. Results: Mean Mini‐Mental State Examination scores in AD patients with WML significantly decreased from 19.4 ± 4.8 to 15.5 ± 6.5 ( P = 0.003). Statistical Parametric Mapping 8 and FineSRT analysis showed more severe and widespread regional cerebral blood flow reduction, mainly in the frontal and mesial temporal regions in AD patients with WML compared with those without WML. Conclusion: Baseline WML could predict a rapid progression of cognitive and brain functional impairment during longitudinal follow up in AD.Geriatr Gerontol Int 2016; 16: 836–842.